1999
DOI: 10.1074/jbc.274.2.735
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D Mediates Matrix Metalloproteinase-9 Secretion in Phorbol Ester-stimulated Human Fibrosarcoma Cells

Abstract: Phospholipase D (PLD) has been implicated in vesicle trafficking in the Golgi and hence secretion. In this study, we show that the secretion of matrix metalloproteinase-9 (MMP-9) from HT 1080 human fibrosarcoma cells was stimulated by phorbol 12-myristate 13-acetate in a time-and dose-dependent manner that involved protein kinase C. The phorbol ester also increased PLD activity in the cells. Evidence that PLD was involved in the stimulation of MMP-9 secretion was provided by the observations that the secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 20 publications
5
51
0
Order By: Relevance
“…These data suggest that the increased expression of MMP in the v-Srctransformed cells is dependent upon RalA and the elevated speci®c activity observed in the v-Rastransformed cells is independent of RalA. Exton and co-workers recently reported that MMP-9 secretion induced by phorbol esters was dependent on PLD and phosphatidic acid production (Williger et al, 1999). It is unlikely that the mechanism was the same as that reported here since phorbol esters activate PLD by activating protein kinase C, which can activate PLD directly (Exton, 1998).…”
Section: The Dominant Negative S28n Rala Mutant Prevents Vsrc and V-rmentioning
confidence: 71%
“…These data suggest that the increased expression of MMP in the v-Srctransformed cells is dependent upon RalA and the elevated speci®c activity observed in the v-Rastransformed cells is independent of RalA. Exton and co-workers recently reported that MMP-9 secretion induced by phorbol esters was dependent on PLD and phosphatidic acid production (Williger et al, 1999). It is unlikely that the mechanism was the same as that reported here since phorbol esters activate PLD by activating protein kinase C, which can activate PLD directly (Exton, 1998).…”
Section: The Dominant Negative S28n Rala Mutant Prevents Vsrc and V-rmentioning
confidence: 71%
“…Corresponding with this concept, very high levels of WBCho in combination with normal PCho have been found in cases with subacute stent thrombosis, sudden death and massive intravascular thrombi [26]. Another potential mechanism responsible for the activation of PLD in the monocyte-macrophage system is the involvement of PLD in the secretion of matrix metallo proteinases [27], which are crucial for causing plaque rupture. Furthermore, a change of PLD expression has been demonstrated in human plaque macrophages being colocalized with oxidation epitopes [28].…”
Section: Discovery Of Choline As a Marker In Acute Coronary Syndromementioning
confidence: 91%
“…Involvement of JNK signaling pathway in regulation of MMP-9 is also reported (Gum et al, 1997). Finally, secretion of newly synthesized MMP-9 from HT1080 human ®brosarcoma cells was regulated by phospholipase D activity (Williger et al, 1999), which may regulate MMP-9 production at a late stage.…”
Section: Introductionmentioning
confidence: 88%